2016
DOI: 10.1080/15384101.2016.1158377
|View full text |Cite
|
Sign up to set email alerts
|

Subnuclear localization, rates and effectiveness of UVC-induced unscheduled DNA synthesis visualized by fluorescence widefield, confocal and super-resolution microscopy

Abstract: Unscheduled DNA synthesis (UDS) is the final stage of the process of repair of DNA lesions induced by UVC. We detected UDS using a DNA precursor, 5-ethynyl-2'-deoxyuridine (EdU). Using wide-field, confocal and super-resolution fluorescence microscopy and normal human fibroblasts, derived from healthy subjects, we demonstrate that the sub-nuclear pattern of UDS detected via incorporation of EdU is different from that when BrdU is used as DNA precursor. EdU incorporation occurs evenly throughout chromatin, as op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…This prompted us to conclude that the unbound YOYO-1 was washed away, but some YOYO-1 stayed bound to the remaining dsDNA. This is in line with our recent finding that even exposing DNA in fixed cells to pH <3, denaturation is not complete ( 46 ). Lastly, similar results have been obtained for other cyanine dyes in the presence of low pH, primary thiols ( Supplementary Figure S2 ), and also in buffers of an increased ionic strength ( Supplementary Figure S3 , discussed in Supplementary Note 1 ).…”
Section: Resultssupporting
confidence: 93%
“…This prompted us to conclude that the unbound YOYO-1 was washed away, but some YOYO-1 stayed bound to the remaining dsDNA. This is in line with our recent finding that even exposing DNA in fixed cells to pH <3, denaturation is not complete ( 46 ). Lastly, similar results have been obtained for other cyanine dyes in the presence of low pH, primary thiols ( Supplementary Figure S2 ), and also in buffers of an increased ionic strength ( Supplementary Figure S3 , discussed in Supplementary Note 1 ).…”
Section: Resultssupporting
confidence: 93%
“…We, as well as others, have shown that EdU is a sensitive marker of replication, with no detectable nonspecific staining or background [33]. Our microscopy system is capable of detecting DNA replication with high sensitivity, therefore the rate of false negative identification of S-phase cells is very low if any.…”
Section: Discussionmentioning
confidence: 87%
“…The proliferation rate was the calculated ratio of the number of cells with nuclei fully incorporated with EdU against the total number of cell nuclei visualized by Hoechst 33342. Meanwhile, loci of EdU partial incorporation in the nuclei indicate unscheduled DNA synthesis, i.e., occurrence of newly synthesized DNA for damage repair [59], was also counted.…”
Section: Edu Incorporation Assaymentioning
confidence: 99%